Effect of Surgical Approach on Length of Stay, Cost, and Early Complication Rate in Total Hip Arthroplasty - Campbell, Joshua C.; Rajaee, Sean S.; Palosaari, Andrew A.; Ju, Derek; Moon, Charles; Paiement, Guy; Penenberg, Brad (The Journal of Hip Surgery, 2022)
Background Total hip arthroplasty (THA) is a historically popular and successful operation. While many steps of the operation are consistent between practitioners, discussion around which approach constitutes the “best” approach for routine, primary THA remains an open question.Objective The purpose of this study was to determine the effects of the surgical approach on hospital length of stay (LOS), hospital costs, and complication rates. A multisurgeon review of a single hospital was conducted to evaluate three surgical approaches: superior (SA), posterior (PA), and direct anterior (DAA).Methods All elective primary THAs performed between July 2013 and July 2016 were reviewed in an administrative database. Two surgeons performed SA, three surgeons performed PA, and two surgeons performed DAA. A total of 1,799 arthroplasties were analyzed: 980 (SA), 685 (PA), and 134 (DAA). Multivariate logistic, Poisson, and linear regression models were used to calculate the effects of each approach on LOS, cost, and per cent discharge home while adjusting for age, severity of illness scores, obesity, and smoking.Results After adjusting for patient characteristics, mean LOS for SA (1.8 days) was lower than both PA (2.4, p < 0.001) and DAA (2.9, p < 0.001), and PA (2.4) was lower than DAA (2.9, p < 0.001). Mean hospital costs were lower for SA than PA ($738 difference, p < 0.001) and DAA ($2,222 difference, p < 0.001), and PA was lower than DAA ($1,420 difference, p < 0.001). Both SA (88.7%) and PA (86.1%) were associated with a higher rate of discharge to home than DAA (78.4%, p = 0.002, p < 0.001, respectively). SA and PA were associated with a lower 30-day readmission (1.3%) compared with DAA (5.2%, p < 0.001) with no difference in 90-day readmissions seen.Conclusion When controlling for patient factors, the SA was associated with a decreased LOS, decreased costs, and increased likelihood of discharge home compared with both the PA and DAA with no increase in 90-day readmissions.
Keywords: total joint arthroplasty; posterior approach; superior approach; anterior approach; surgical outcomes